Pharmacologic treatment in patients with COVID-19: an integrative review - Vargas, María Rubi (Universidad de Sonora, 2021)
Introduction: Today more than ever human health has been compromised; humanity is suffering from the invasion of the SARS-CoV-2 coronavirus, which has exposed the world to the worst health emergency in this century. Although the scientific community and global health systems are joining efforts in the search for a definitive treatment, to date it is recognized that the therapy is aimed at mitigating the symptoms. Objective: Identify scientific evidence on pharmacological treatment for patients with COVID-19. Methodology: An integrative review of literature published from December 2019 to October 2020, in the following information systems Clinical Key, Dialnet, EBSCO Host and Scopus was performed using the descriptors Coronavirus Infections, COVID-19, Drug therapy, and pharmacological treatment. The selection criteria were quantitative research articles of any type of design, in English and Spanish, available in full text, obtaining a sample of 24 articles. Results: Most of the studies were integrative reviews with a percentage of 66.6 and clinical or in vitro trials with a percentage of 12.5. Nine drugs of major use in COVID-19 were identified in the drug therapy, that is, Hydroxychloroquine/Chloroquine, Lopinavir/Ritonavir, Remdesivir, Azithromycin, Ivermectin, Tocilizumab and Dexamethasone. However, According to the scientific evidence only four drugs showed significant effectiveness. Conclusions: Remdesivir demonstrated greater effectiveness and safety during the treatment, and Tocilizumab and Dexamethasone showed favorable results. Nevertheless, the results are not conclusive. The authors pointed out that so far is not possible to conclude there are treatments that effectively fight COVID-19.